Effect of maltodextrin and arabic gum in water vapor sorption thermodynamic properties of vacuum dried pineapple pulp powder - Gabas, A. L.; Telis, V. R. N.; Sobral, P. J. A.; Telis-Romero, J. (Elsevier B.V., 2007)
Moisture equilibrium data of pineapple pulp (PP) powders with and without additives - 18% maltodextrin (MD) or 18% gum Arabic (GA) - were determined at 20, 30, 40 and 50 degrees C by using the static gravimetric method in a water activity range of 0.06-0.90. The obtained isotherms were sigmoid, typical type 111, and the Guggenhein-Anderson-de Boer (GAB) model was fitted to the experimental data of equilibrium moisture content versus water activity. Addition of additives was shown to affect the isotherms in such a way that, at the same water activity, samples PP + GA and PP + MD presented lower equilibrium moisture content and were not so affected by varying temperature. The net isosteric heats of sorption of pulp powders with additives were higher (less negative) than those of pineapple pulp powders, suggesting that there are more active polar sites in the product without addition of GA or MD. An empirical exponential relationship could describe the heat of sorption dependence on the material moisture content. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: isotherm; maltodextrin; Gum arabic; heat of sorption; water activity